Planning and management of the coastal environment of Chancay - Cabrera, Carlos (2000)
The planning and management of the coastal environment of Chancay is an expression of integrated planning and management of natural resources. This coastal environment is endowed with renewable resources, notably: productive fisheries, industries, beaches; However, there are factors that alter these ecosystems, such as population growth, environmental pollution, unemployment, among others. This work makes known the environmental analysis and environmental planning through the generation and evaluation of alternatives that may lead to the implementation of programs and actions in the city of Chancay.